Taxation of pesticide use as a tool to achieve the objectives of the Common Agricultural Policy – the Danish model - Bieluk, Jerzy (Przegląd Prawa Rolnego, 2024)
Denmark started to implement taxation mechanisms aimed at reducing pesticide use already in the 1980s. The most recent reform of 2013 significantly increased the tax burden and tied tax rates to the level of harmfulness caused by a given measure used in agricultural production, and its negative impact on the environment as well as human health. This solution has proved to be effective and has led to a significant reduction in the use of pesticides. This Danish experience shows, on the one hand, that achieving a reduced use of pesticides in agriculture is not an easy process and requires a simultaneous application of solutions to achieve social acceptance, while on the other hand, that a well-regulated tax system can be an excellent tool for achieving socially desirable goals, including a significant reduction in the use of the most harmful pesticides and a significant reduction also in the use of the less harmful ones. However, in countries that do not use taxation aimed at reducing the pesticide use, it is after all society that bears the external costs of using plant protection products, which include the loss of biodiversity or the pollution of drinking water or soil etc.